Papal Letters of Indulgence and their Role as a Means of Obtaining Donations for Hispanic Monasteries and Convents in the Late Middle Ages (Edad Media. Revista de Historia, 2025)
This article critically examines the demand and utilization of papal indulgence letters by traditional monasteries and new mendicant convents in the years 1198-1314. The primary objective is to evaluate how these letters facilitated the acquisition of alms from the faithful and thus improve their economic situation. The analysis reveals that the newly established religious orders in particular exerted every effort to obtain these “bullae” and to establish themselves in late medieval society. At this time, they obtained hundreds of such “litterae pontificiae”, from which they derived substantial financial resources that were instrumental in the renovation or construction of new churches and religious centres.
Keywords: Alms; Papal documents; Indulgences; Monasteries and convents